Analysis of Factors Causing in The Crease in Sexual Harrasment of Female Students on Campus - Harahap, Rustam; Baehaqi, Ja'far (Al-Qanun: Jurnal Kajian Sosial dan Hukum Islam, 2023)
Sexual harassment is something done by someone of the opposite sex and the victim feels uncomfortable with it. There are still many reports of sexual harassment in the world of education, especially in higher education, which occurs against female students. This research aims to analyze what factors can increase the occurrence of sexual harassment in the campus environment. The method used in this research is (library research) by looking at several previous studies related to this research. As a result, there are several factors that can increase the occurrence of sexual harassment in the campus environment. The factor that often occurs with female students on campus is that the perpetrator has the power (power ratio) to subdue the victim.